Global Jurist (De Gruyter, 2001)
Global Jurist offers a forum for scholarly cyber-debate on issues of comparative law, law and economics, international law, law and development, and legal anthropology. Edited by an international board of leading comparative law scholars from all the continents, Global Jurist is mindful of globalization and respectful of cultural differences.